2007
DOI: 10.1093/ndt/gfm323
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of matrix metalloproteinase inhibitor ONO-4817 on morphological alterations in chlorhexidine gluconate-induced peritoneal sclerosis rats

Abstract: It appears that the administration of the MMP inhibitor ONO-4817 might be a new approach to the amelioration of PS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
40
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 16 publications
4
40
0
Order By: Relevance
“…Ro et al have reported that the MMP inhibitor ONO-4817 controlled angiogenesis, infiltration of macrophage, and peritoneal fibrosis in rat models of peritoneal sclerosis [10], which suggests the possibility of protection from peritoneal injury by inhibition of MMP-2 activities. Angiotensin-converting enzyme (ACE) inhibitors have been shown to have inhibitory effects on MMP-2 activity [45,46].…”
Section: Protection From Peritoneal Injury By Inhibition Of Mmp-2mentioning
confidence: 98%
See 4 more Smart Citations
“…Ro et al have reported that the MMP inhibitor ONO-4817 controlled angiogenesis, infiltration of macrophage, and peritoneal fibrosis in rat models of peritoneal sclerosis [10], which suggests the possibility of protection from peritoneal injury by inhibition of MMP-2 activities. Angiotensin-converting enzyme (ACE) inhibitors have been shown to have inhibitory effects on MMP-2 activity [45,46].…”
Section: Protection From Peritoneal Injury By Inhibition Of Mmp-2mentioning
confidence: 98%
“…In rodent models of peritoneal injury, the development of EPS was analyzed by injecting the antiseptic chlorhexidine gluconate into the peritoneal cavity to induce inflammation [7][8][9][10][11]. In this model, MMP-2 levels in the peritoneal effluent and MMP-2 gene expression in the peritoneum correlated with changes in thickness of the peritoneum, inflammation, D/D0 glucose levels, and net ultrafiltration.…”
Section: Production Of Mmp-2 In Animal Models Of Peritoneal Injurymentioning
confidence: 99%
See 3 more Smart Citations